Getting started with Windows VDI : create, maintain, and secure scalable and resilient virtual desktops with Windows 8.1 and Windows Server 2012 R2 /: create, maintain, and secure scalable and resilient virtual desktops with Windows 8.1 and Windows Server 2012 R2. (2014) - Fryer, Andrew
No abstract available